The Role of Knowledge Adoptive Capacity towards Exports Performance: An Evidence from Textile Sector - Ramaisa Aqdas; Nik Ab Halim Nik Abdullah (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose - Knowledge absorptive capacity plays a significant role in export performance. It is a dynamic capability that firms apply to gain competitiveness in today’s knowledge-based economies. The aim of the present research is to identify relationship among dimensions of KAC and export performance. Design/Methodology - Nature of study was descriptive and quantitative. Data was collected through questionnaires from 291 large scale textile firms of Pakistan. Smart PLS was used in analyzing data by incorporating CFA and SEM techniques to test the hypotheses. Findings - The results reveal that knowledge acquisition, transformation, and exploitation have significant positive relationship with export performance.